Harmony 404: a society undeciphered - Mokhtar, Nor Zainiyah Norita (SINGAPORE INTERNATIONAL PRESS, 2017)
Harmony 404: a society undeciphered is a compilation of work written by a group of Malaysian youths who aspire to share their experiences and observations of a nation they call home. The compilation of work consists of various aspects of life that they have found inspiring. The written work hope to inspire other nations to share their aspirations in breaking cultural barriers and upholding solidarity within a multiethnic nation.